A Comparison of Methamphetamine Users to a Matched NHANES Cohort: Propensity Score Analyses for Oral Health Care and Dental Service Need - Murphy, Debra A. (J Behav Health Serv Res, 2016)
Dental problems are among the most frequently reported health issues of drug users. This study describes, among the largest population of methamphetamine (MA) users to date (N = 459, including both HIV-negative and HIV-positive participants): oral hygiene practice, dental care access, and dental quality of life. A matched control group from the Third National Health and Nutrition Examination Survey was utilized. Findings conclusively establish that MA users have severe oral health deficits compared to the general population: they are 3.5 times more likely to experience painful toothaches, 6.6 times to experience difficulty eating, and 8.6 times to be self-conscious due to dental appearance. HIV-positive users were more likely to have regular dental visits than HIV-negative users. Severity of use (both high frequency use as well as injection as the method) was associated with poorer oral health care. Despite the magnitude of the need, few MA users receive the needed care.